2013
DOI: 10.11648/j.pbs.20130205.12
|View full text |Cite
|
Sign up to set email alerts
|

″Smoking Kills″ Vs. ″Smoking Makes Restless″: Effectiveness of Different Warning Labels on Smoking Behavior

Abstract: Warning labels on cigarette packages rely on the negative health aspects of smoking. For smokers, however, smoking is related to positive as well as to negative outcomes. Positive smoking outcomes are shown to be crucial in activating smoking behaviour. Thus, this study compared current health warnings with warning labels contradicting positive outcomes. In a field study, 38 adult smokers were followed over a 5-day period to investigate the effect of the different types of warning labels on actual smoking beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Research on the effectiveness of tobacco warning labels has provided evidence that warning labels that contradict positive smoking outcome expectancies have changed implicit attitudes, selfreported outcome expectancies, and smoking behavior (Glock, Unz, & Kovacs, 2012). Those warning labels also turned out to be more effective than the current health-related warning labels (Glock et al, 2013b). Thus, this study was aimed at investigating the effectiveness of health-related alcohol warning labels and of warning labels that contradicted positive outcome expectancies (positive-related).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the effectiveness of tobacco warning labels has provided evidence that warning labels that contradict positive smoking outcome expectancies have changed implicit attitudes, selfreported outcome expectancies, and smoking behavior (Glock, Unz, & Kovacs, 2012). Those warning labels also turned out to be more effective than the current health-related warning labels (Glock et al, 2013b). Thus, this study was aimed at investigating the effectiveness of health-related alcohol warning labels and of warning labels that contradicted positive outcome expectancies (positive-related).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, we did not look at behavioral effect which the present warning labels might have, but only investigated their influence on explicit cognitions and implicit associations. This can be problematic because research has shown that often, the attitude-behavior link is rather weak (Glock et al, 2013c). Therefore, the use of behavioral measures is highly recommended by different scholars in the field (e.g., Kok et al, 2017) in order to be able to make clear predictions about the effectiveness of different kinds of warning labels.…”
Section: Discussionmentioning
confidence: 99%